Pengaruh Kompetensi Sumber Daya Manusia, Motivasi Kerja, dan Kepuasan Kerja terhadap Kualitas Pelayanan Pegawai Kantor Kecamatan se-Kota Semarang - Alivia, Putri; Raharjo, Teguh Hardi (Business and Accounting Education Journal, 2024)
This research aims to analyze the influence of human resource competence, work motivation and job satisfaction on the service quality of employees of sub-district offices throughout the city of Semarang. This research is a quantitative research with a population of 1320 sub-district office employees throughout Semarang City. The number of samples in this study was 93 respondents which was calculated using the Slovin formula. The sampling technique uses techniques Propotionate Random Sampling. The data collection technique uses a questionnaire method. The data analysis technique uses the classical assumption test, multiple linear regression analysis, model feasibility test, hypothesis test, coefficient of determination test and descriptive statistical analysis of percentages using the IBM SPSS 26 program. The results of the multiple linear regression analysis obtained data namely Y = 9.776 + 0.590X1 + 0.082 X2 + 0.142X3 + e. The results of the research show that human resource competence has a positive and significant influence on the quality of employee service, while work motivation and job satisfaction do not have a significant influence on the quality of service for employees of sub-district offices throughout Semarang City.